Estimated SARS-CoV-2 Seroprevalence in Healthy Children and Those with Chronic Illnesses in the Washington Metropolitan Area as of October 2020. Issue 7 (July 2021) - Bahar, Burak; Simpson, Joelle N.; Biddle, Cara; Campbell, Andrew; Dome, Jeffrey S.; DeBiasi, Roberta L.; Mowbray, Catriona; Marguilies, Stefanie; Sherman, Adrienne; Reuben, Jacqueline; Delaney, Meghan
Abstract : The estimated severe acute respiratory syndrome coronavirus 2 seroprevalence in children was found to be 9.46% for the Washington Metropolitan area. Hispanic/Latinx individuals were found to have higher odds of seropositivity. While chronic medical conditions were not associated with having antibodies, previous fever and body aches were predictive symptoms.